Self-perceived Impact of Glaucomatous Visual Field Loss and Visual Disabilities on Driving Difficulty and Cessation. Issue 11 (November 2018) - Tam, Alex L.C.; Trope, Graham E.; Buys, Yvonne M.; Yang, Yelin; Shen, Carl; Jin, Ya-Ping
Abstract : Purpose: To investigate if glaucoma severity and the presence of self-reported glare and difficulty with dark adaptation are associated with driving difficulty or cessation. Patients and Methods: Individuals with glaucoma, age 50+ and visual acuity in the better eye ≥20/50 were included. Glaucoma severity was defined by the visual field mean deviation (MD) in the better eye and was classified into 2 groups: mild (MD>−6 dB) and moderate/severe (MD⩽−6 dB). Patient responses to the glare and dark adaptation subscales in Glaucoma Quality of Life-15 questionnaire were used to measure relevant visual disability. Associations were assessed utilizing prevalence ratios (PR). Results: A total of 99 participants (57% female) were included with 19% (19/99) reporting driving cessation. Patients with moderate/severe glaucoma when compared with mild glaucoma reported a significantly higher percentage of driving cessation (33% vs. 8%; P =0.002), presence of glare (27% vs. 6%; P =0.012), and difficulty with dark adaptation (31% vs. 10%; P =0.011). Individuals with self-perceived difficulty with dark adaptation were about 4 times more likely than those without to have difficulty driving at night (adjusted PR=3.94; P <0.0001) or in poor driving conditions (adjusted PR=4.09; P =0.0002). Self-reported glare was associated with an increased risk of driving difficulty in poor driving conditions (PR=4.17; P =0.05). Conclusions: Patients with moderate/severe glaucomatous visual field loss reported significantly higher percentage of driving cessation, presence of glare and difficulty with dark adaptation. Difficulty with dark adaptation was significantly associated with difficulty driving at night or in poor driving conditions. Further studies are needed to confirm these findings.